2012
DOI: 10.1371/journal.pone.0047217
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammation Disrupts the LDL Receptor Pathway and Accelerates the Progression of Vascular Calcification in ESRD Patients

Abstract: BackgroundChronic inflammation plays a crucial role in the progression of vascular calcification (VC). This study was designed to investigate whether the low-density lipoprotein receptor (LDLr) pathway is involved in the progression of VC in patients with end-stage renal disease (ESRD) during inflammation.Methods and ResultsTwenty-eight ESRD patients were divided into control and inflamed groups according to plasma C-reactive protein (CRP) level. Surgically removed tissues from the radial arteries of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 19 publications
2
21
1
Order By: Relevance
“…The results suggest that the balance of food intake and fecal excretion in casein injection group was roughly equivalent to that in the control and HFD group. Our previous in vivo and in vitro studies demonstrated that inflammatory stress disrupted cholesterol homeostasis through dysregulation of the LDLr pathway and exacerbated the progression of atherosclerosis, vascular calcification, and liver injury 14, 18, 19. Therefore, inflammatory stress may induce lipid redistribution from the circulation to the cardiac tissues, thereby causing hypolipidaemia and cardiac fibrosis 20.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that the balance of food intake and fecal excretion in casein injection group was roughly equivalent to that in the control and HFD group. Our previous in vivo and in vitro studies demonstrated that inflammatory stress disrupted cholesterol homeostasis through dysregulation of the LDLr pathway and exacerbated the progression of atherosclerosis, vascular calcification, and liver injury 14, 18, 19. Therefore, inflammatory stress may induce lipid redistribution from the circulation to the cardiac tissues, thereby causing hypolipidaemia and cardiac fibrosis 20.…”
Section: Discussionmentioning
confidence: 99%
“…In ESRD patients, Liu et al (56) found that TNF-␣ and monocyte chemotactic protein-1 (MCP-1) could increase BMP2 and decrease SM ␣-actin expressions via disrupting the LDL receptor pathway, and this change significantly accelerated the progression of AC. Similarly, in CKD rat models, it was demonstrated that inflammation (TNF-␣, IL-1␤, IL-6) enhanced BMP2 and decreased SM ␣-actin expressions through activating MAPKs and phosphatidylinositol 3-kinase signaling pathways (2).…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 99%
“…25,26 FIGURE 2. The in vitro study revealed that serum obtained from patients with ESRD induced type I collagen expression in rat aortic VMSCs in a concentration-dependent manner, which could be attributed to the phenotypic modulation of rat aortic VSMCs that was induced by uremic toxins in the patients' serum.…”
Section: Discussionmentioning
confidence: 99%